Ban smoking during Ramadan - Hasan, Md. Mahmudul (New Straits Times Press (M) Bhd., 2019)
REMEMBER once, as I was about to enter a mosque in Penang, I saw the imam smoking hurriedly before he walked in to lead the Zohor prayer.